Digital Marketing Strategy and Sales of Household Products in Pari Urban Village: A Case Study - Sanny, Annisa; Ritonga, Husni Muharram; Suwarno, Suwarno; Putri, Indah Febriani (Universitas Negeri Medan, 2023)
This study aims to help the inhabitants of Kota Pari Village, PantaiCermin District, SerdangBedagai Regency by developing and implementing marketing strategies through digital marketing medium to boost sales of household products. To ensure that the domestic industry's products are well-known and in demand beyond the immediate area, this study aims to educate the local community on how to effectively promote them via digital marketing. A positive and statistically significant impact of marketing tactics on digital marketing was found in this study. The sales of common consumer goods are significantly impacted by marketing efforts. Household goods sales are significantly impacted for the better by digital marketing. The internet marketing of household products benefits greatly from strategic marketing. In Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency, it is intended that household industry actors will be able to learn about and implement digital marketing strategies in order to boost their sales and revenue.